Analysis of slotted p-detection multi-channel and random multi-access protocol for wireless communication network - LIU Bin-bin; ZHAO Dong-feng; DING Hong-wei (Tongxin xuebao)
The slotted p-detection multi-channel and random multi-access （SPMRM） protocol was preseted. This SPMRM protocol can provided multimedia traffic through load equilibrium and multi-priority and p-detection multi-channel, and ensured the wireless channel-utilizing rate. Furthermore, a mathematical model was used to analyze the throughput of SPMRM protocol. The efficiency of the new protocol was validated by theoretical analysis and com-puter simulation. In other words, the simulation results of SPMRM protocol is better than a continuous-time p-detection multi-channel and random multi-access protocol.